A Case Study On Malaysian Airline System Berhad - Thurairajah, Jayakumar (2006)
The paper identifies and carefully diagnose the current condition in mAS particularly in year 2005 as manifested by its external and internal environment s so that appropriate strategic action can be recommended in line with the company's strategic intent and strategic mission.